1997
DOI: 10.1046/j.1365-294x.1997.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of populations of the threatened eastern massasauga rattlesnake, Sistrurus c. catenatus: evidence from microsatellite DNA markers

Abstract: Throughout its distribution in North America, the threatened eastern massasauga rattlesnake (Sistrurus c. catenatus) persists in a series of habitat-isolated disjunct populations of varying size. Here, we use six microsatellite DNA loci to generate information on the degree of genetic differentiation between, and the levels of inbreeding within populations to understand how evolutionary processes operate in these populations and aid the development of conservation plans for this species. Samples were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
72
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 15 publications
8
72
0
1
Order By: Relevance
“…Measures of genetic differentiation (I= 0.890; F ST = 0.059) showed that there was a moderate degree of population division between the Taim and the Vargas site. Similar and lower values of F ST , which showed significant population division, were also found in other species (see HARTL & CLARK, 1989;GIBBS et al, 1997;ESCORZA-TREVIÑO & DIZON, 2000;TRUJILLO et al, 2004;WURFF et al, 2005). A homogeneity χ 2 test confirmed the population division of L. longicaudis (P< 0.001; α'= 0.01) after a Bonferroni correction for multiple testing (RICE, 1988), and the Lut457 (χ 2 = 24.27; P< 0.001) and Lut715 e Hardy-Weinberg equilibrium; *significant at the level of α'= α/5 = 0.01 after Bonferroni correction for multiple tests (RICE, 1988) Genotyping at more than one locus was possible only in 81.5% of the scored samples, from which 37% were evaluated for more than three loci.…”
Section: Resultssupporting
confidence: 74%
“…Measures of genetic differentiation (I= 0.890; F ST = 0.059) showed that there was a moderate degree of population division between the Taim and the Vargas site. Similar and lower values of F ST , which showed significant population division, were also found in other species (see HARTL & CLARK, 1989;GIBBS et al, 1997;ESCORZA-TREVIÑO & DIZON, 2000;TRUJILLO et al, 2004;WURFF et al, 2005). A homogeneity χ 2 test confirmed the population division of L. longicaudis (P< 0.001; α'= 0.01) after a Bonferroni correction for multiple testing (RICE, 1988), and the Lut457 (χ 2 = 24.27; P< 0.001) and Lut715 e Hardy-Weinberg equilibrium; *significant at the level of α'= α/5 = 0.01 after Bonferroni correction for multiple tests (RICE, 1988) Genotyping at more than one locus was possible only in 81.5% of the scored samples, from which 37% were evaluated for more than three loci.…”
Section: Resultssupporting
confidence: 74%
“…Deviation from Hardy-Weinberg is usually attributed to null alleles (Gopalakrishnan et al 2004;Garcia de Leon et al 1995), selection (Garcia de Leon et al 1995), grouping of gene pools (Walhund effect; Gibbs et al 1997), inbreeding or nonrandom mating (Beaumont and Hoare 2003). Nine of the ten primer pairs in C. dussumieri indicated positive F IS values in different populations.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, human disturbance could affect the survival and dispersal of neonates, which in turn could affect population age and genetic structure and viability. Thus, it is interesting in this regard that the massasauga rattlesnake population in Killbear Provincial Park shows significant genetic structure over distances <2 km, indicating very restricted gene flow (Gibbs et al 1997). Whether human disturbance has contributed to this phenomenon is unknown, but the fact that the snakes respond to disturbance by restricting their movement makes this a possibility worth investigating.…”
Section: Discussionmentioning
confidence: 99%